The invisible Camorra: Neapolitan crime families across Europe - Allum, Felia (Cornell University Press, 2016)
Local motives, global choices -- Functional mobility -- Camorra clans in Germany and the Netherlands: Hof, Hamburg, and Amsterdam -- Camorra clans in France: La Seyne-sur-mer, Paris, and Villeneuve Loubet -- Camorra clans in Spain: Granada, Tarragone, and Tenerife -- Camorra clans in the UK: Preston, London, and Aberdeen